2020
DOI: 10.1021/acsapm.0c00845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solubility Difference of Tackifier to Respective Components of Block Copolymers on Microphase-Separated Structures in Coated Layers of Pressure-Sensitive Adhesive Prepared by Solution Coating Process

Abstract: Effects of solubility difference of tackifier to respective components of block copolymers on microphase-separated structures were examined using coated layers of the polystyrene-block-polyisoprene-blockpolystyrene triblock copolymer and polystyrene-block-polyisoprene diblock copolymer blend, which forms spherical microdomains of polystyrene (PS) in the polyisoprene (PI) matrix, mixed with three types of tackifiers: aliphatic (C5) resin, aliphatic−aromatic (C5−C9) resin, and rosin ester (RE) resin. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…In the current study, we revealed the effects of solubility difference of the tackifier to the respective components of block copolymers on mechanical properties for the same SIS/SI-tackifier specimens used in our previous study . For this purpose, the stress–strain, shear force, and stress-relaxation measurements at various stretching ratios were performed.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In the current study, we revealed the effects of solubility difference of the tackifier to the respective components of block copolymers on mechanical properties for the same SIS/SI-tackifier specimens used in our previous study . For this purpose, the stress–strain, shear force, and stress-relaxation measurements at various stretching ratios were performed.…”
Section: Introductionmentioning
confidence: 73%
“…Although further reducing the total A fraction from the above-stated case with the A-spherical microdomains suggests seemingly nothing of interest because of no further morphological transition expected, even for this case, it was found in our previous study that controlling the size of the A-spheres was possible. Actually, it was found that the A-spheres became smaller upon the addition of the B-component favorable tackifier molecules . For this particular case, it is also expected that the mechanical properties change (reduction of the tensile modulus/acceleration of the stress relaxation) because the fraction of the loop conformation of the B-block chains is increased while the fraction of their bridge conformation is complementarily decreased.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Usually, it is very difficult to clarify these two phase structures simultaneously by SAXS analysis. Although, Doi et al 25 investigated the phase structure of styrenic block copolymer/tackifier blend by SAXS analysis, they clarified only the influence of tackifier on the phase structure of block copolymer. In our next report, we are going to investigate the phase structure of PBA/RE tackifier blend as a model system using SAXS.…”
Section: Resultsmentioning
confidence: 99%